Analisis Supremasi Nilai-nilai Moderasi Beragama di Lembaga Pendidikan Islam - Misbahul Muslih; Saihan Saihan; Mas'ud Mas'ud; Yudi Ardian Rahman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study wants to analyze and reveal how the supremacy pattern is based on strengthening and internalizing the values of religious moderation in madrasas. This study uses a descriptive qualitative approach by exploring relevant information through interviews, observations, and documentation through the selection of informants who are considered capable and understand the case, in order to reveal in depth the existing curriculum development patterns. The results of this study show that the pattern carried out in strengthening the values of religious moderation in madrasah tsanawiyah miftahul ulum Jember is pursued in several aspects. First, the internalization of a tolerant attitude, second, the internalization of an attitude of anti-violence, third, the internalization of an accommodating attitude towards local wisdom, and fourth, the internalization of an attitude of militancy in the nation, which in all aspects is carried out based on an attitude of responsibility and continuity with collaboration between the madrasah starting from educators and educators with student guardians and the surrounding community.